2016
DOI: 10.1136/jech-2015-206939
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent mental health and earnings inequalities in adulthood: evidence from the Young-HUNT Study

Abstract: Adolescent mental health problems reduce adult earnings, especially among individuals in the lower tail of the earnings distribution. Preventing mental health problems in adolescence may increase future earnings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 35 publications
4
39
0
1
Order By: Relevance
“…Subsequent studies have confirmed that being currently diagnosed with any psychiatric condition is linked to a reduced probability of being employed or actively engaged in the labour market (Banerjee et al, 2015;Chatterji et al, 2011). Psychological problems during childhood have also been shown to forecast long-term economic outcomes including sustained reductions in income (Evensen et al, 2017;Goodman et al, 2011) and an elevated probability of unemployment (Egan et al, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Subsequent studies have confirmed that being currently diagnosed with any psychiatric condition is linked to a reduced probability of being employed or actively engaged in the labour market (Banerjee et al, 2015;Chatterji et al, 2011). Psychological problems during childhood have also been shown to forecast long-term economic outcomes including sustained reductions in income (Evensen et al, 2017;Goodman et al, 2011) and an elevated probability of unemployment (Egan et al, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Adolescent boys with mental health problems report negative consequences such as poor psychological function, and low subjective wellbeing and self-esteem, poor social relationships and school problems (Derdikman-Eiron et al, 2012;Derdikman-Eiron et al, 2011). Mental CONTACT Marie Dahlen Granrud marie.granrud@inn.no health problems among adolescent boys may have serious long-term consequences such as dropping out of school (Hetlevik, Bøe, & Hysing, 2018) and higher education (Hjorth et al, 2016), which may lead to reduced earnings in adulthood (Evensen, Lyngstad, Melkevik, Reneflot, & Mykletun, 2017). Other consequences are an increased risk for substance abuse (Bakken, 2018), suicidal ideation (Taliaferro & Muehlenkamp, 2014) and, in the worst-case scenario, suicide (Wasserman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This may result in more externalising disorders, such as antisocial personality disorders and substance abuse or dependence among young men [50,51]. Young women, on the other hand, report more internalizing disorders such as depression [2] and anxiety [51][52][53].…”
Section: Prevalence Of Mental Distress and Gendermentioning
confidence: 99%
“…Despite the apparent greater prevalence of mental distress among women and accompanying underlying mechanisms, studies show that externalizing behaviour, more common in men, may be more damaging in the long run, possibly affecting the ability to get a job and build a family later in life [51,52]. Thus, although levels of mental distress during adolescence and young adulthood are higher among women than among men, the long-term effects in today's society may be more severe for men.…”
Section: Prevalence Of Mental Distress and Gendermentioning
confidence: 99%